Strategi Ibu Single Parent dalam Menjalani Multi Pekerjaan Informal Untuk Mewujudkan Kesejahteraan Anak (Studi Kasus di Desa Mojo Kecamatan Mojo Kabupaten Kediri) - Maylafa Iza Nareta Mercusuar Susilo; Arief Sudrajat (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The phenomenon of single mothers working multiple informal jobs is a common social reality in rural areas, including Mojo Village, Mojo District, Kediri Regency. Divorce or the death of a spouse places single mothers in the position of primary breadwinner and child care provider, necessitating specific strategies to ensure their children's well-being. This study aims to analyze the strategies employed by single mothers in working multiple informal jobs to ensure their children's well-being and to identify the obstacles they face. This study employed a qualitative approach with a case study method. Data collection involved observation, in-depth interviews, and documentation of five single mothers working multiple informal jobs in Mojo Village. Data analysis employed the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The research's analytical framework utilizes a Marxist-Socialist Feminist perspective to examine the interrelationships between women's dual roles, productive and reproductive work, and class and gender relations in the informal sector. The research findings indicate that single mothers' strategies for achieving child well-being include engaging in multiple informal jobs as an economic strategy, managing time and the dual role of work and childcare, managing finances oriented toward children's needs, and utilizing social networks.